Citra Merek, Kepuasan Konsumen, dan Harga: Mendorong Perilaku Pembelian Ulang Kopi Keliling SJ - Aisyah, Siti; Harijanto, Jusuf (Jurnal Riset Manajemen dan Bisnis, 2024)
This study aims to provide an explanation of how the independent variables, namely brand image and price, influence the dependent variable, namely repurchase intention with the intervening variable, namely consumer satisfaction. This study uses a quantitative method by distributing questionnaires as a sampling. This study was measured using the help of SmartPLS software version 4.0. The population of this study is the East Jakarta community who have consumed Kopi Keliling SJ more than twice. This study uses a non-probability sampling technique, which can be understood as drawing limited or specific samples with certain considerations to obtain samples with the desired characteristics. The data used in this study are primary data obtained from questionnaires. The results of the study prove that the variables of brand image and consumer satisfaction have a direct effect on repurchase intention, but price does not have a direct effect on repurchase intention. Price has a direct effect on consumer satisfaction, but brand image does not have a direct effect on consumer satisfaction. consumer satisfaction is able to indirectly mediate price on repurchase intention. However, consumer satisfaction is not able to indirectly mediate brand image on repurchase intention.